Metagenomic next-generation sequencing in a diagnosis of Pneumocystis pneumonia in an X-linked immunodeficient child: a case report - Qing, Lu; Zhao, Yufei; Zhang, Ye; Guan, Yuanlin; Lu, Guoyan (Frontiers in Pediatrics, 2023)
Background: The diagnosis of Pneumocystis pneumonia (PCP) remains challenging in certain specific clinical situations. Metagenomic next-generation sequencing (mNGS), as a novel diagnostic method, may help in the diagnosis of PCP. Case Presentation: A 6-month-old child developed acute pneumonia and sepsis. This child had previously suffered from Escherichia coli septicemia and was cured. However, the fever and dyspnea relapsed. Blood tests revealed a low lymphocyte count (0.69 × 109 /L) and acute inflammatory markers, such as high level procalcitonin (8.0 ng/mL) and C-reactive protein (19 mg/dL). Chest imaging showed inflammation and decreased translucency in both lungs, but no thymus shadow. Various serology tests, 1,3-beta-D-glucan test, culture, as well as sputum smear failed to detect any pathogens. mNGS using blood identified 133 specific nucleic acid sequences of Pneumocystis jirovecii, suggesting an infection with this pathogen. After treatment with trimethoprim-sulfamethoxazole for 5 days, the patient's conditions improved, but ventilator treatment was still needed. The child passed away due to respiratory failure after the parents decided to abandon treatment. The family disagreed to perform an autopsy, so an anatomical diagnosis could not be obtained. Whole exome sequencing suggested X-linked immunodeficiency. A hemizygous mutation of c.865c > t (p.r289 *) was detected in the IL2RG gene, which was inherited from the mother (heterozygous state). Conclusion: This case report highlighted the value of mNGS in diagnosing PCP when conventional diagnostic methods fail to identify the agent. Early onset of recurrent infectious diseases may indicate the presence of an immunodeficiency disease, and timely genetic analysis and diagnosis are crucial.